Prodromus of a fern flora for Bolivia. XXXII. Athyriaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis to the fern family Athyriaceae in Bolivia, comprising the genera Athyrium, with two species, and Diplazium, with 30 species. The latter genus includes seven species endemic to Bolivia and presents numerous taxonomic problems. One new species, D. exindusiatum M.Kessler & A.R.Sm., is described.